The 6th International Research Symposium in Service Management (IRSSM-6) - Voon, Boo Ho (UiTM Sarawak, 2016)
The 6th International Research Symposium in Service Management (IRSSM-6) was successfully organised by Universiti Teknologi MARA (UiTM) Sarawak from 11th to 15th August 2015 in Kuching (Sarawak, Malaysia). The theme for IRSSM-6 was "Service Imperatives in the New Economy: ServiceExcellence for Sustainability".